Investigation of progress co-precipitation ferum(II) and nickel(II) of polyhydroxocomplexes - Фролова, Лілія Анатоліївна (Science-based technologies, 2020)
Nanodispersed ferrites obtained by the hydrophase method are promising materials due to their high adsorption, catalytic, and magnetic properties. Over the years, the focus has been on the development of high temperature production technologies. According to the literature review, the most promising of the ferrite preparation methods are hydrophase technologies, which accommodates the co-precipitation of hydroxides from salt solutions and further ferritization. There is a many work considering the co-precipitation processes of layered double hydroxides (LDH) occurring in the case of the presence of two and trivalent cations. With the used of potentiometric titration, cyclic voltamperometry (CVA), the mechanism of formation of polyhydrocomplexes is established. It is showed that the process of coprecipitation occurs in several stages - the first stage is the formation of polyhydroxocomplexes. The CVA obtained at a molar ratio of n = [OH-/[M2+] = 0 indicate that the aquacomplexes of the corresponding metal ions form separate stable hydrolysis products. At a molar ratio of n = [OH-/[M2 +] = 1 in Ni2+- Fe2+ -SO42- - H2O systems, the course of the curves practically does not change for cycles 1-5, which indicates that the electrode processes velocity is much greater than the destruction rate of polynuclear hydroxocomplexes. This, in turn, is a consequence of the stability of the particles formed. The peak of the anode branch of the curve in the potential range 1.3-1.6V has a symmetric peak in the cathode region. The cathodic reduction wave with potentials 0.25-0.3V on the cathodic branch of the CVA practically does not change with increasing number of cycles. This may be due to the reduction together with Ni2 + ions of Fe2+ ions, which can also bind to stable heteronuclear complexes. The slight increase in the peaks indicates that in this case stable polynuclear particles are formed which are isomorphic to the ferrite structure.